The Anglo-Portuguese alliance and the English merchants in Portugal, 1654-1810 - Shaw, L. M. E. (Ashgate, 1998)
The English-Portuguese alliance of 1654 lasted for 156 years. Interweaving politics, economics, religion and commerce to portray what life was like for English merchants in Portugal, this work is the result of many years of archival research.